The female tennis serve: an analagous version of the male serve? - Elliott, B.; Whiteside, D.; Lay, B.; Reid, M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The mechanics of the high-performance male tennis serve have received considerable research attention; however, the relevance of this knowledge to the female serve is largely unknown. To address this research void, 3D body, racquet and ball kinematics were recorded from eight professional female players hitting a `first-power` serve, using a 22-camera VICON MX system operating at 500 Hz. The kinematic data were then compared with the corresponding male data in the literature that have been garnered from high-performance players. The female mean resultant racquet velocity was 0.86 of the value reported for male players, which mirrored the ratio of the highest velocity serve recorded on the respective professional circuits. While the majority of kinematic variables were similar between these two groups, the lesser shoulder internal rotation by the females (0.83) compared with the males helps to define the above velocity difference.